STRUCTURE OF ECAP ALUMINIUM AFTER DIFFERENT NUMBER OF PASSES - Ilucová, Lucia; Saxl, Ivan; Svoboda, Milan; Sklenička, Václav; Král, Petr (Image Analysis and Stereology, 2011)
The structure of high purity (99.99%) aluminium processed by equal channel angular pressing in the as pressed state after different number of passes was examined using various stereological methods. An extreme inhomogeneity and complicated anisotropy was observed along the body of rod-like specimens.